THE ROLE OF CONSUMER REVIEWS IN BEHAVIOR AND LOYALTY - Yuniar, Anira; Pebrianggara, Alshaf; Almanfaluti , Istian Kriya; Yulianto , Mochamad Rizal (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of Influencer Review, Affiliate Marketing, and Content Marketing on Sales. Method: The validity test shows that all variables have an r-count > r-table (0.361), indicating they are valid. The reliability test using Cronbach's Alpha of 0.621 confirms that the data is reliable. Multiple regression analysis with a partial test (t-test) reveals that all independent variables positively affect sales, with t-count values for X1 (6.114), X2 (23.588), and X3 (23.078) > t-table (1.697) and a significance level of 0.00. Results: The coefficient of determination test (R Square 0.988) indicates that 98.8% of sales variability can be explained by influencer review, affiliate marketing, and content marketing, while 1.2% is influenced by other factors. Novelty: Thus, this study confirms that digital marketing strategies through influencer reviews, affiliate marketing, and content marketing significantly contribute to increasing sales.